Advancing Marine Engineering Literacy Through Green Technology Integration: Competency Development for Alternative Fuel Systems and Hybrid Propulsion - Mardiana; Pantjadjatmika Rachmardata; Arief Supriatna; Octi Avriani; Rikman Sohriadhana (Meteor STIP Marunda, 2025)
The maritime industry's transition toward IMO 2050 decarbonization targets demands a fundamental transformation in marine engineering education to address alternative fuel systems and hybrid propulsion technologies. This qualitative study examines competency development requirements through the perspectives of industry experts, maritime academy lecturers, and recent marine engineering graduates across Indonesian maritime institutions. Employing thematic analysis and cross-group comparisons, the research identifies critical literacy components encompassing LNG, methanol, and ammonia fuel systems; hybrid electric propulsion; alternative fuel safety protocols; and green technology maintenance competencies. Findings reveal significant gaps between industry requirements and current curricula, particularly in practical training infrastructure, faculty expertise, and troubleshooting skill development. The study proposes a comprehensive competency framework integrating green technology literacy with traditional thermodynamic foundations, emphasizing faculty development, industry partnerships, and phased curriculum integration. Results demonstrate that strategic coordination across institutional, industry, and policy dimensions is essential for preparing marine engineers capable of supporting maritime decarbonization initiatives while maintaining operational excellence in increasingly complex propulsion systems.